Impact of Corporate Tax Cuts on Corporate Investment - Changwoo Nam (Korea Development Institute (KDI), 2016)
- There has been growing public support for a tax hike as corporate investment remains stagnant despite the recent cut in the corporate tax rate. Accordingly, this study aims to closely examine the impact of the corporate tax rate on investment. - Managerial decisions, including those on investment, are based on a diverse range of factors, encompassing not only the corporate tax rate but also financial conditions and investment uncertainties. As such, corporate characteristics must be controlled, when possible, before estimating the impact of corporate tax change on investment. - An empirical analysis found that Korea's listed companies expand their investment significantly when the corporate tax rate is reduced. - For the robustness of the analysis results, this study adopted various models and methodologies to analyze listed companies in 2002-2014 and found that a 1%p cut in the average effective corporate tax rate caused the investment rate to increase by 0.2%p. - In particular, it can be assumed that such an increase in investment may have been higher if the managements' tunneling activities were curtailed. ·An analysis, using a structural model, revealed that in Korea, management sought private interests nine times more than their counterparts in the US, diminishing the effects of a tax cut by roughly 28% in the short run. - Therefore, the government must take a cautious approach when increasing the corporate tax rate, and also strengthen the internal and external monitoring and supervision of management to enable companies to make reasonable investment decisions.
Keywords: 330